(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Life gets easier when you have electricity; electricity has many advantages like lightning heating, cooling and transportation systems. Ninety-seven per cent of our world’s electricity runs the socio-economic living. However, electricity is expensive in the Philippines. The proposal of CD as a solar generator can help Filipinos lessen their bills every month, and it can be good for our earth in preventing climate change. The research design used for the study was quantitative experimental research while utilizing a purposive sampling technique. The statistical treatment used for this study was–a test to determine the difference between the two groups of respondents. Using the survey questionnaire as the research instrument, the researchers surveyed to identify the level of acceptability of the CD as an Alternative to Solar Panels regarding construction materials, designs and procedures, and presentation. The study’s respondents are 5 Mechanical Engineering Students and Electrical Engineering Students. The following procedures were undertaken in developing the model: preparing the floor plan and materials. The results of the study in terms of construction materials, designs and procedures, and presentation are as follows. The acquired overall mean of the Mechanical Engineering Students was 3.63, interpreted as highly acceptable. Electrical Engineering Students have an overall mean of 3.69, interpreted as highly acceptable. The critical was 2.78, and the t-computed was 2.13. It indicates no significant difference between the assessments of the two groups of respondents. For further improvement of the project, the respondents recommended that the researchers spend a lot of time to finish the project and make a blueprint to make the project even better.